Aesthetics in the relationship of conceptual metaphors and cultural models in the translation of Rubayyat of Khayyam - Panahbar, Ehsan; Hesabi, Akbar; Pirnajmuddin, Hussein (Penerbit Universiti Kebangsaan Malaysia, 2016)
Mandelblit’s cognitive translation hypothesis investigates the translatability of metaphors at the conceptual level by considering two possible alternatives of same mapping condition (SMC) and different mapping condition (DMC) facing translators. His model incorporating other ideas about cultural models presumes conceptual metaphors as intertwined with cultural models. Additionally, in philosophy aesthetics has been defined as a way to access truth (constructed, situated and embodied rather than absolute). Therefore, the aim of the present study is to aesthetically evaluate Khayyam’s Rubayyat and its English translation by Whinfield as a case study in order to gauge the issue of aesthetic equivalence with regard to the integrated model based on ideas of Mandelblit, Tabakowska, and Al-Zoubi et al. Thus, firstly, SMCs and DMCs are investigated in Whinfield’s translation and secondly, aesthetic experiences of the two cultures involved are evaluated in terms of conceptual metaphors; finally, an attempt is made to modify the integrated model in terms of aesthetics. The research findings reveal that the translator has been mostly successful in maintaining conceptual equivalence by changing generic schemas and cultural models compatible to his Western community in cases of DMCs. This indicates the interrelation of conceptual metaphors and cultural models and demonstrates the overall applicability of the integrated model. Also confirmed is the necessity of supplementing the said model by factoring in aesthetics, defined by Heidegger and Nietzsche as the very understanding of a community about realities.